Detection of Later Stage Breast Cancer in First Nations Women in Ontario, Canada - Sheppard, Amanda J. (Can J Public Health, 2010)
OBJECTIVE: To compare the distribution of stage at breast cancer diagnosis between First Nations (FN) and non-FN women, and to investigate factors associated with later diagnosis in FN women. METHODS: A case-case design was employed to compare FN women (N=287) to a frequency-matched random sample of women (N=671) from the general population diagnosed with breast cancer in the Ontario Cancer Registry. Women were matched (2:1) on period of diagnosis (1995–1999, 2000–2004), age at diagnosis (<50 vs. ≥50), and Regional Cancer Centre (RCC). Stage and data relevant to the determinants of stage were collected from medical charts at the RCCs. The association between stage (stage II+ vs. I) and FN status was modeled using logistic regression analyses; for FN women, the association between risk factors and stage was examined. RESULTS: FN women (66%) were diagnosed with a later stage significantly more often than non-FN women (56%). FN women with a non-screened cancer (OR 5.03, 95% CI 2.48–10.21) and those who were overweight or obese (OR 2.98, 95% CI 1.27–6.98 and OR 4.46, 95% CI 1.95–10.21, respectively) were significantly more likely to be diagnosed at a later stage. Having a comorbidity reduced the odds of a later stage (OR 0.51, 95% CI 0.27–0.96) in FN women. CONCLUSION: This study demonstrates the need for FN women, in particular those who are not accessing the health care system, to participate in breast screening programs aimed at detecting breast cancers earlier with a better prognosis. These findings suggest that the cancer care system in Ontario should better target this population through increasing awareness and access to screening.